2017
DOI: 10.1080/10641963.2016.1267200
|View full text |Cite
|
Sign up to set email alerts
|

Screening of cardiovascular risk factors in patients with schizophrenia and patients treated with antipsychotic drugs: are we equally exhaustive as with the general population?

Abstract: Schizophrenia (SZ); Treatment with antipsychotic drugs (TAD); Cardiovascular risk factor/s (CVRF); Without schizophrenia but on therapy with antipsychotic drugs (NS-TAD); Defined Daily Dose (DDD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 25 publications
0
2
0
2
Order By: Relevance
“…Antipsychotic-induced weight gain is a leading cause of noncompliance, leading to increased risk for relapse 3 , 4 . Moreover, obesity is also linked to greater morbidity, mortality, and decreased life expectancy due to an increased risk for cardiovascular and malignant disorders 5 8 . Being obese can affect psychological well-being, leading to lower quality of life 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Antipsychotic-induced weight gain is a leading cause of noncompliance, leading to increased risk for relapse 3 , 4 . Moreover, obesity is also linked to greater morbidity, mortality, and decreased life expectancy due to an increased risk for cardiovascular and malignant disorders 5 8 . Being obese can affect psychological well-being, leading to lower quality of life 9 .…”
Section: Introductionmentioning
confidence: 99%
“…No presente estudo, todos os artigos analisados foram publicados no idioma inglês e em periódicos da área médica e da epidemiologia. A maioria dos estudos é originária dos Estados Unidos , da China [39][40][41][42][43][44][45][46] , da Espanha [47][48][49][50][51][52][53][54] , da Austrália [55][56][57][58] e da Inglaterra [59][60][61][62][63][64] . Os principais achados são em relação a alterações glicêmicas e lipídicas, síndrome metabólica, hipertensão, obesidade/ganho de peso e morbidade cardiovascular e serão detalhados em tópicos.…”
Section: Resultsunclassified
“…Oito artigos associaram a HAS com os fármacos utilizados para o tratamento da esquizofrenia 32,37,48,50,65,67,69,75 . A maior prevalência de HAS foi evidenciada por um estudo, assim como os menores índices de HDL-colesterol -fator protetivo às doenças cardiometabólicas 67 .…”
Section: Hipertensão Arterial Sistêmica (Has)unclassified
“…Primary care practitioners are ideally placed to screen for smoking and arrange appropriate treatment; however, studies have shown lower rates of screening in primary care for tobacco use in people with schizophrenia than in the general population. 10 …”
Section: Cardiometabolic Risk Factorsmentioning
confidence: 99%